2011
DOI: 10.1371/journal.pone.0026998
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Reveals an Integrated Immune Response in Nucleated Erythrocytes

Abstract: BackgroundThroughout the primary literature and within textbooks, the erythrocyte has been tacitly accepted to have maintained a unique physiological role; namely gas transport and exchange. In non-mammalian vertebrates, nucleated erythrocytes are present in circulation throughout the life cycle and a fragmented series of observations in mammals support a potential role in non-respiratory biological processes. We hypothesised that nucleated erythrocytes could actively participate via ligand-induced transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 25 publications
5
119
0
Order By: Relevance
“…In fact, the transcription of rtxA1 3 was upregulated when the bacteria were cocultured with either granulocytes or erythrocytes, but only if the bacterium and eukaryotic cell were in contact (104). Interestingly, the eel erythrocytes were able to agglutinate the rtxA1 3 deficient strain, which suggests that fish erythrocytes can exert a defensive role against bacterial pathogens as suggested by Morera et al (106). In the light of these results, the authors hypothesized that RtxA1 3 is expressed as a defense mechanism against cells from the innate immune system, destroy them and trigger a cytokine storm that could cause the death of the animals by septic shock.…”
Section: Toxinsmentioning
confidence: 79%
“…In fact, the transcription of rtxA1 3 was upregulated when the bacteria were cocultured with either granulocytes or erythrocytes, but only if the bacterium and eukaryotic cell were in contact (104). Interestingly, the eel erythrocytes were able to agglutinate the rtxA1 3 deficient strain, which suggests that fish erythrocytes can exert a defensive role against bacterial pathogens as suggested by Morera et al (106). In the light of these results, the authors hypothesized that RtxA1 3 is expressed as a defense mechanism against cells from the innate immune system, destroy them and trigger a cytokine storm that could cause the death of the animals by septic shock.…”
Section: Toxinsmentioning
confidence: 79%
“…For chicken erythrocytes, thrombocytes as well as bone-marrow-derived DCs, macrophages, and monocyte-derived macrophages, it was already shown that they react to immune stimuli by, e.g., up-or downregulation of chemokine receptors and induction of IFN-γ (Morera et al 2011;St Paul et al 2012a;St Paul et al 2012b;St Paul et al 2012c;Wu and Kaiser 2011). We could confirm that chicken spleen cells incubated with PMA/ionomycin and concanavalin A showed an induction of IFN-γ mRNA and the stimulation was further documented by a strong cell proliferation after PMA/ionomycin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These transcripts were found to encode transcription factors, signal transduction proteins, cytokines and chemokines, complement factors, proteins involved in apoptosis and proteolysis, proteins with anti-microbial activities, as well as many known or novel proteins not previously linked to the immune response. Additionally, RNA-Seq analysis of Poly (I:C) (polyinosinic:polycytidylic acid)-challenged rainbow trout erythrocytes revealed diverse groups of differentially expressed mRNA transcripts related to multiple physiological systems including the endocrine, reproductive, and immune systems (Morera et al, 2011).…”
Section: Quantifying Transcript Levelmentioning
confidence: 99%